2022
DOI: 10.1038/s41586-022-05085-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for phosphorus limitation on Amazon forest productivity

Abstract: The productivity of rainforests growing on highly-weathered tropical soils is expected to be limited by phosphorus (P) availability 1 . Yet, controlled fertilisation experiments have failed to demonstrate a dominant role for P in controlling tropical forest net primary productivity (NPP). Recent syntheses have demonstrated that responses to N addition are as large as to P 2 , and adaptations to low P availability appear to allow NPP to be maintained across major soil P gradients 3 . Thus, the extent to which P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 68 publications
2
49
0
Order By: Relevance
“…Dry biomass accumulation and growth rates in diameter and height are parameters that have already been applied to several tropical tree species in order to analyze and understand the balance between, and the levels of, nutrients in the soil and in the plant [ 23 , 39 ]. In this context, the plant responses almost always suggest that their physiological performance is limited by P [ 9 , 40 ]. This reinforces the hypothesis that B. excelsa , despite having high growth rates in relation to other native and exotic species, even in places with low availability of P, is limited by P. Thus, P fertilization in B. excelsa plantations can provide a considerable increase in production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry biomass accumulation and growth rates in diameter and height are parameters that have already been applied to several tropical tree species in order to analyze and understand the balance between, and the levels of, nutrients in the soil and in the plant [ 23 , 39 ]. In this context, the plant responses almost always suggest that their physiological performance is limited by P [ 9 , 40 ]. This reinforces the hypothesis that B. excelsa , despite having high growth rates in relation to other native and exotic species, even in places with low availability of P, is limited by P. Thus, P fertilization in B. excelsa plantations can provide a considerable increase in production.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ]. Not coincidentally, soil availability of P has been used to explain variations and limitations in forest biomass and growth across the Amazon basin [ 7 , 8 , 9 ]. However, the question of whether plants will fulfill the P demand for an increase in biomass under elevated CO 2 conditions remains to be answered [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lugli et al (2020) found increasing fine root production with increasing soil P but did not report relative allocation of fine roots to leaves, so we do not know if their relationship was due to an increase in total production (including fine root production) or whether biomass partitioning changed. Cunha et al (2022) reported strong increase of NPP exclusively with P fertilization, and fine root production was found to have greater response to P increase than canopy production (29% and 19%, respectively). Their findings showed a preferred biomass allocation to root when P availability increases, which is what our model with a "pos" parametrization simulates.…”
Section: Model Validationmentioning
confidence: 93%
“…In previously published versions of the model, r2l is a constant. Because several fertilization studies found that fine root production increases with soil P (Waring et al, 2019;Lugli et al, 2021;Cunha et al, 2022), we modified the code so that r2l would be related to soil soluble P (psol, unit: gP / kg soil) following:…”
Section: Model Modificationsmentioning
confidence: 99%
See 1 more Smart Citation